IMPROVING VOCABULARY MASTERY AND DISTINGUISHING VOCABULARY THROUGH LISTENING TO AUDIO-VISUAL - Rosa, Dela; Asgara, Eqy Yudha; Suryaman, Maman (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This research design is from an experimental study. The goal of this research is to see if using audio-visual aids in increasing student vocabulary. The pretest and prost test are data collection equipment. The exam was intended to collect data in order to determine the impact of audio-visual use. The results showed that: 1. The use of audio visual can increase the number of students' abilities in listening to dialogue, 2. Students can distinguish vocabulary with the same pronunciation but different meanings. That ability was increase, after learning to use audio visual. They are better in their listening to audio.